Therapeutic plasma exchange in patients with pauciimmune vasculitis: Hospital Universitario San Ignacio experience; Bogotá, Colombia - Juan P. Córdoba; Kateir Contreras; Maite Hurtado; Jessica Pinto; Martha P. Rodríguez1; Carolina Larrarte (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2014)
Introduction: The vasculitis ANCAS positive, are a group of diseases with different clinical manifestations. Therapeutic plasma exchange has become an excellent tool for the treatment of these patients in specific conditions. Objective: Describe the demographic and clinical characteristics of patients and the final outcomes in patients with positive ANCAS vasculitis that required therapeutic plasma exchange (TPE). Materials and methods: All patients under 18 years old with positive ANCAS vascultiis that required TPE where included during the period of May 2010 and December 2013. Results: 13 patients where treated, with a total of 73 TPE sessions. The average age was 52,3 years (Range 17 to 70). The principal diagnosis for interventions was rapidly progressive glomerulonephritis (RPGN) plus alveolar hemorrhage (63%). The average number of sessions per patient was 5,6 (range 1 a 10) with an average of plasma volume exchange per session of 1,26 (range 0.72 a 1,56). Of the 13 patients, 11 (84,6%) required renal replacement therapy (RRT) during hospitalization. At discharge, 36.3% recover the renal function, 27% continue on RRT and 36,3% died. There was at least one complication in 6,8% of all sessions. Conclusions: TPE is an excellent tool to treat patients with positive ANCAS vasculitis that present with RPGN, high levels of serum creatinine or dialysis need, or alveolar hemorrhage. This is a safe procedure with comparable results according to International literature.Key words: Apheresis, plasmapheresis, therapeutic plasma exchange, vasculitis, ANCA.